2000
DOI: 10.1007/s004310051281
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen storage disease type Ia: recent experience with mutation analysis, a summary of mutations reported in the literature and a newly developed diagnostic flowchart

Abstract: Increased knowledge of the genetic basis of glycogen storage disease type I provides a DNA-based diagnosis, prenatal DNA-based diagnosis in chorionic villus samples and carrier detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
46
1
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 42 publications
6
46
1
1
Order By: Relevance
“…GSD Ia is thus, as previously reported, genetically heterogeneous (Chevalier-Porst et al, 1996;Lei et al, 1995;Rake et al, 2000). Most patients are compound heterozygotes.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…GSD Ia is thus, as previously reported, genetically heterogeneous (Chevalier-Porst et al, 1996;Lei et al, 1995;Rake et al, 2000). Most patients are compound heterozygotes.…”
Section: Resultssupporting
confidence: 56%
“…Since the cloning of the gene encoding G6Pase (G6PC, GDB:231927), almost 60 mutations have been reported, thus illustrating the genetic heterogeneity of the disease (for review, see : Rake et al;2000). Here we report the identification of 93/96 mutant alleles in 48 patients with GSD Ia.…”
Section: Introductionmentioning
confidence: 91%
“…The deficiency of G6Pase activity is caused by mutations in the gene encoding this enzyme [42,189,[225][226][227]. In their 1999 review paper [226], Chou and Mansfield mentioned 31 distinct mutations identified in a total of 128 patients.…”
Section: Gsd Type Iamentioning
confidence: 99%
“…In this model, the combined activities of the G6P translocator and G6P phosphatase would concentrate glucose in the ER lumen, permitting an efficient second efflux route which would be active, allowing the export of glucose into the serum against a concentration gradient. As of yet, all cases of type I glycogen storage diseases are linked to defects in either the glucose-6-phosphatase or the G6P translocase gene, suggesting that mutations in glucose transport across the ER membrane are lethal or that ER transport systems are functionally redundant (28,30,35).…”
mentioning
confidence: 99%